Optimization and transfer of robust primary drying protocols for biopharmaceuticals through lyophilization process modeling - Brecht Vanbillemont; Andrea Arsiccio; Tim Menzen; Andrea Hawe (AAPS Open)
Abstract Lyophilization, or freeze-drying, is a widespread process for stabilizing (bio)pharmaceutical products. The primary drying phase is resource-intensive, making its optimization a focal point for improving economic and environmental sustainability. Mechanistic modeling of the primary drying phase has emerged as a key tool for designing robust processes, identifying optimal critical process parameters, and minimizing failure modes such as product collapse, uncontrolled pressure increase, or incomplete sublimation. This study extended the traditional modeling frameworks by incorporating an uncertainty analysis to account for process variability originating from process parameters and material attributes. Model validation and verification activities were performed to establish model credibility. The ensuing risk assessment quantified the failure mode probabilities. This methodology was capable of ensuring process robustness at a pilot scale freeze-dryer by construction of a regulatory compliant design space and the establishment of proven acceptable ranges. An iterative approach to collect process knowledge was conducted by updating the dried layer resistance estimates while verifying the design space. The transfer of the normal operating ranges to a commercial scale freeze-dryer was assisted by the model and was experimentally verified. Experimental results confirmed the model’s capability to predict process parameter combinations yielding acceptable critical quality attributes while minimizing process time. The model provides a scientific rationale for process parameters selection and can support in the process optimization, robustness assessment and process transfer activities necessary for a regulatory submission. Graphical Abstract